2022
DOI: 10.3389/fmed.2022.886868
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Dependent Glycolysis-Driven Lipogenesis Supports Proliferation and Survival of Human Pulmonary Arterial Smooth Muscle Cells in Pulmonary Hypertension

Abstract: Hyper-proliferation of pulmonary arterial vascular smooth muscle cells (PAVSMC) is an important pathological component of pulmonary vascular remodeling in pulmonary arterial hypertension (PAH). Lipogenesis is linked to numerous proliferative diseases, but its role in PAVSMC proliferation in PAH remains to be elucidated. We found that early-passage human PAH PAVSMC had significant up-regulation of key fatty acids synthesis enzymes ATP-citrate lyase (ACLY), acetyl-CoA carboxylase (ACC), and fatty acid synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“… 3 HIF-1α and HIF-2α are differentially expressed in IPAH PASMCs and PAECs. 28 We found reduced SIRT7 expression in PAH PAECs might be due to hyperactivation of HIF-2α. The imbalance of TGF-β signalling caused by BMPR2 loss is involved in vascular remodelling during PH, and increased TGF-β level and Smad3 signalling activation were observed in both PH patients and rodent models.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 3 HIF-1α and HIF-2α are differentially expressed in IPAH PASMCs and PAECs. 28 We found reduced SIRT7 expression in PAH PAECs might be due to hyperactivation of HIF-2α. The imbalance of TGF-β signalling caused by BMPR2 loss is involved in vascular remodelling during PH, and increased TGF-β level and Smad3 signalling activation were observed in both PH patients and rodent models.…”
Section: Discussionmentioning
confidence: 64%
“…>HIF-2α has been reported to be specifically induced by hypoxia in PAECs. 28 We found that overexpression of HIF-2α suppressed SIRT7 expression, while knockdown of HIF-2α abolished the suppression of SIRT7 by hypoxia (see Supplementary material online , Figure S3C – F ).…”
Section: Resultsmentioning
confidence: 78%
“…The importance of lipid mechanism in PH ( Siques et al, 2020 ; Xu, Janocha & Erzurum, 2021 ) has been demonstrated, and imbalanced fatty acid metabolism is reported in the heart and lungs of PAH patients ( Hernandez-Saavedra et al, 2020 ; Zhao et al, 2014b ; Zhuang et al, 2019 ). A higher rate of de novo fatty acid synthesis was found in PAH-HPASMC, and increased expression of FASN was observed in the lungs of MCT-treated rats ( Singh et al, 2016 ) and human PAH pulmonary arterial vascular smooth muscle cells (PAVSMC) ( Jiang et al, 2022 ). In addition, another fatty acid synthesis enzyme ACLY was also upregulated in PAVSMC ( Jiang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A higher rate of de novo fatty acid synthesis was found in PAH-HPASMC, and increased expression of FASN was observed in the lungs of MCT-treated rats ( Singh et al, 2016 ) and human PAH pulmonary arterial vascular smooth muscle cells (PAVSMC) ( Jiang et al, 2022 ). In addition, another fatty acid synthesis enzyme ACLY was also upregulated in PAVSMC ( Jiang et al, 2022 ). Furthermore, another study reveals that inhibition of FASN is beneficial for endothelial function in PH ( Singh et al, 2017 ) and improves cardiac function associated with PH ( Singh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell isolation, characterization, and maintenance were performed under Pulmonary Hypertension Breakthrough Initiative‐approved protocols, as described previously. 28 , 29 , 30 , 31 Cells were maintained in complete PromoCell Smooth Muscle Cell Growth Medium 2 with SupplementPack and Antibiotic‐Antimycotic. Before experiments, cells were incubated for 48 hours in basal media supplemented with 0.1% BSA (for immunoblot lysates) or with 0.2% FBS (for RNA isolation).…”
Section: Methodsmentioning
confidence: 99%